Ytterbium complexes with 2-(tosylamino)-benzylidene- N -(2-halobenzoyl)-hydrazones for solution-processable NIR OLEDs - Tcelykh, Liubov O.; Vashchenko, Andrey A.; Medved'ko, Aleksei V.; Marciniak, Łukasz; Aleksandrov, Alexey E.; Goloveshkin, Alexander S.; Lepnev, Leonid S.; Latipov, Egor V.; Burlov, Anatoly S.; Utochnikova, Valentina V. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2022)
A series of ytterbium complexes with halogenated 2-(tosylamino)-benzylidene- N -(2-benzoyl)-hydrazones was obtained for NIR OLED applications. Halogenation resulted in a significant solubility increase, while the photophysical and electronic properties of the obtained complexes almost coincided. High solubility, mobility of charge carriers and, most importantly, the efficiency of luminescence made it possible to successfully use the obtained complexes as host-free emitting layers in a series of OLED devices. The efficiency of the obtained devices correlates with the halogen mass when thick emissive layers are deposited. However, a layer thickness decrease results in an efficiency increase, which for thin layers correlates with charge carrier mobility, the only halogen-dependent parameter. The highest efficiency of pure ytterbium luminescence was reached for the complex with Br-substituted ligands and equaled 430 μW W −1 , which is the highest value obtained to date for Yb-based OLEDs.